Fine particle, resin composition and article

Fine particles made from carbon dioxide-based ethylene carbonate structures address dispersibility and disassembly challenges, enabling easy separation and recyclability by releasing carbon dioxide upon heating.

JP2025019469APending Publication Date: 2025-02-07LINTEC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023123094
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing adhesive technologies, particularly those using thermally expandable microspheres, struggle with dispersibility and thin layer formation, and lack options for easy disassembly and recycling, especially when carbon dioxide is not utilized as a raw material.

Method used

Development of fine particles made from carbon dioxide as a raw material, incorporating an ethylene carbonate structure that decomposes upon heating to release carbon dioxide, facilitating easy separation of bonded components.

Benefits of technology

The fine particles enable easy disassembly of bonded components by releasing carbon dioxide at the interface, reducing adhesion and promoting recyclability while minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019469000001_ABST
    Figure 2025019469000001_ABST
Patent Text Reader

Abstract

To provide novel fine particles produced using carbon dioxide as a raw material, a resin composition containing the fine particles, and an article produced using the resin composition.SOLUTION: The present invention provides fine particles containing a (meth)acrylic acid ester polymer comprising, as a monomer unit constituting the polymer, an ethylene carbonate-containing acrylic monomer with an ethylene carbonate structure represented by formula (1).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to microparticles, a resin composition containing the microparticles, and an article manufactured using the resin composition. [Background technology]

[0002] Organic fine particles are used in a wide range of applications, including as additives such as antiblocking agents, toner additives, powder coatings, water-dispersed coatings, decorative plate additives, artificial marble additives, cosmetic fillers, chromatography column fillers, and matting agents, as well as in resin films, coatings, adhesives, and pressure sensitive adhesives.

[0003] In recent years, from the viewpoint of environmental consideration, there has been a demand for electronic devices, electrical appliances, etc. that can be easily disassembled when no longer needed (easy disassembly). The parts generated by disassembly can be recycled or reused.

[0004] For example, when components constituting a product are bonded together with an adhesive sheet, the adhesiveness of the adhesive sheet is reduced by an external stimulus, making it easier to separate and peel the components from each other. As an example of such an adhesive sheet, Patent Document 1 discloses a heat-expandable removable adhesive tape that maintains high normal adhesive strength when bonded, but when separating or dismantling the bonded parts, the adhesive strength is reduced by heating, allowing easy separation and dismantling. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2014-214208 A Summary of the Invention [Problem to be solved by the invention]

[0006] The average particle size of the thermal blowing agent (particularly the thermally expandable microspheres) disclosed in Patent Document 1 is generally about 1 to 80 μm from the standpoint of dispersibility, thin layer formability, etc., which cannot be adequately used depending on the application of the pressure-sensitive adhesive sheet.

[0007] Furthermore, easy dismantling is sometimes required even for products that do not use adhesive sheets, and in such cases, the adhesive sheet disclosed in Patent Document 1 cannot adequately meet the requirements.

[0008] Furthermore, in recent years, with the growing demand for the creation of a recycling-based society, gases such as carbon dioxide, methane, and carbon monoxide have been attracting attention as sustainable carbon raw materials. For example, it has been reported that aliphatic polycarbonates that have only aliphatic (non-aromatic) groups in the main chain can be produced by copolymerizing carbon dioxide and epoxide, and there is growing interest in chemical products and their manufacturing technologies that use gases such as carbon dioxide as raw materials. Carbon dioxide is considered to be a cause of global warming, so the effective use of carbon dioxide emitted from factories in the process of making various materials is useful for environmental protection.

[0009] Therefore, there is a demand for further options for organic microparticles that use carbon dioxide as a manufacturing raw material and enable easier dismantling for easier handling.

[0010] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide novel microparticles produced using carbon dioxide as a production raw material, a resin composition containing the microparticles, and an article produced using the resin composition. [Means for solving the problem]

[0011] In order to achieve the above object, first, the present invention provides a polymer comprising a monomer unit represented by the following formula (1): [ka] The present invention provides fine particles containing a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the following formula (Invention 1).

[0012] In the microparticles according to the above invention (Invention 1), the ethylene carbonate structure present in the (meth)acrylic acid ester polymer can be produced using carbon dioxide as a production raw material, and therefore carbon dioxide can be effectively utilized. In addition, the ethylene carbonate structure is decomposed by heat treatment together with a catalyst, and carbon dioxide is released. Therefore, even if a resin film (adhesive layer, etc.) formed using the above microparticles as a material is in close contact with another object, the carbon dioxide accumulates at the interface between the resin film and the object, thereby reducing the adhesion. As a result, it becomes possible to use the microparticles in applications where the resin film can be easily separated from the object.

[0013] In the above invention (Invention 1), the (meth)acrylic acid ester polymer preferably contains, as a monomer unit constituting the polymer, the ethylene carbonate-containing monomer in an amount of 50% by mass or more and 99.9% by mass or less (Invention 2).

[0014] In the above inventions (Inventions 1 and 2), the ethylene carbonate-containing acrylic monomer is preferably a compound represented by the following formula (2) or (3) (Invention 3). [ka] (In the formula, n represents an integer of 0 or more.) [ka] (In the formula, n represents an integer of 0 or more.)

[0015] In the above inventions (Inventions 1 to 3), the (meth)acrylic acid ester polymer preferably contains acrylic acid as a monomer unit constituting the polymer (Invention 4).

[0016] In the above inventions (Inventions 1 to 4), the average particle size is preferably 10 nm or more and 1 μm or less (Invention 5).

[0017] In the above inventions (Inventions 1 to 5), it is preferable to produce an emulsion containing the (meth)acrylic acid ester polymer as a dispersoid by emulsion polymerization of monomer units containing the ethylene carbonate-containing acrylic monomer, and then to pulverize the residue obtained by removing the dispersion medium constituting the emulsion (Invention 6).

[0018] Secondly, the present invention provides a resin composition (Invention 7) containing the fine particles (Inventions 1 to 6).

[0019] Thirdly, the present invention provides an article (Invention 8) comprising a resin film formed from the resin composition (Invention 7).

[0020] In the above invention (Invention 8), it is preferable that the resin film is an adhesive layer and the article is an adhesive sheet (Invention 9). Effect of the Invention

[0021] The microparticles according to the present invention have a small environmental impact because they are produced using carbon dioxide as a raw material. Furthermore, the microparticles according to the present invention are decomposed by heat treatment together with a catalyst to release carbon dioxide, providing a new means for realizing easy dismantling by blending them in various resins. [Brief description of the drawings]

[0022] [Figure 1] 1 is a SEM image of the microparticles produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of the present invention will be described. [Fine particles] The fine particles according to the present embodiment are formed by polymerizing a monomer unit represented by the following formula (1): [ka] The (meth)acrylic acid ester polymer contains an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the formula:

[0024] The ethylene carbonate structure can release carbon dioxide by decomposition. In particular, when an anion having nucleophilicity is present together with the ethylene carbonate structure, the anion performs a nucleophilic attack on a carbon atom constituting a carbonyl group in the ethylene carbonate structure, thereby efficiently decomposing the ethylene carbonate structure and releasing carbon dioxide.

[0025] By using the microparticles according to the present embodiment having such properties, it is possible to manufacture a product with excellent dismantling properties. That is, the carbon dioxide released from the microparticles can be used to reduce the adhesion between the members constituting the product, and as a result, the product can be easily dismantled. For example, when members are bonded together by an adhesive sheet manufactured using the microparticles as one of the materials, the carbon dioxide is generated by the decomposition of the ethylene carbonate structure described above, and the carbon dioxide is stored at the interface between the adhesive sheet and the member, and the adhesive sheet and the member can be physically separated.

[0026] In addition, the above-mentioned nucleophilic anion is preferably generated from a nucleophilic anion generator capable of generating nucleophilic anions by a specific stimulus. In particular, when a nucleophilic anion generator that generates the above-mentioned anion by heating is used, the product in which the microparticles according to the present embodiment are used can be disassembled by heating as an external stimulus.

[0027] 1. (Meth)acrylic acid ester polymer The (meth)acrylic acid ester copolymer in this embodiment is not particularly limited as long as it contains, as a monomer unit constituting the polymer, an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the above formula (1).

[0028] The ethylene carbonate-containing acrylic monomer is not particularly limited as long as it contains an ethylene carbonate structure and has a (meth)acryloyl group (structure). A preferred example of the ethylene carbonate-containing acrylic monomer is a (meth)acrylic acid ester having a structure in which an organic group having an ethylene carbonate structure is bonded to a (meth)acryloyloxy group. An example of such a (meth)acrylic acid ester is represented by the following formula (2): [ka] or an acrylic acid ester represented by the following formula (3): [ka] or a methacrylic acid ester represented by the following formula (4): [ka] In any of the formulas (2) to (4), n and m are integers of 0 or more, and X is hydrogen or a methyl group.

[0029] Among the (meth)acrylic acid esters represented by the above formula (2) and formula (3), from the viewpoint of easy and favorable release of carbon dioxide gas, (meth)acrylic acid esters in which n and m are each 1 or more are preferred, and (meth)acrylic acid esters in which n and m are each 2 or more are preferred. The upper limit of each of the above n and m is not particularly limited, but from the viewpoint of polymerizability, it is preferably 10 or less, more preferably 6 or less, particularly preferably 4 or less, and even more preferably 3 or less. Among these, (meth)acrylic acid esters in which n=1 are preferred, and in particular, (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate in which n=1 in formula (3) is preferred. The ethylene carbonate-containing monomer may be used alone or in combination of two or more.

[0030] As disclosed in JP 2006-335971 A, the ethylene carbonate-containing monomer can be produced by adding CO2 to the epoxy group of a (meth)acrylate having an epoxy group to introduce a carbonate group. That is, the (meth)acrylic acid ester copolymer according to the present embodiment using the ethylene carbonate-containing monomer can be produced using carbon dioxide as a production raw material, and therefore carbon dioxide can be effectively utilized.

[0031] From the viewpoint of effectively using carbon dioxide as a production raw material, the (meth)acrylic acid ester copolymer in this embodiment preferably contains 50% by mass or more of ethylene carbonate-containing acrylic monomer, particularly preferably contains 80% by mass or more, and more preferably contains 85% by mass or more. In addition, the (meth)acrylic acid ester copolymer in this embodiment preferably contains 99.9% by mass or less of ethylene carbonate-containing acrylic monomer, particularly preferably contains 99.5% by mass or less, and more preferably contains 99.0% by mass or less. By having a content of 99.9% by mass or less, the (meth)acrylic acid ester copolymer contains sufficient other constituent monomers, and the (meth)acrylic acid ester copolymer is likely to have the desired performance.

[0032] The (meth)acrylic acid ester copolymer in this embodiment may contain a monomer other than the above-mentioned ethylene carbonate-containing acrylic monomer as a monomer unit constituting the polymer. For example, examples of the monomer include (meth)acrylic acid alkyl esters having an alkyl group with 1 to 12 carbon atoms; monomers containing reactive functional groups such as hydroxyl groups, carboxyl groups, and amino groups; (meth)acrylic acid esters containing alkoxyalkyl groups; (meth)acrylic acid esters having aromatic rings such as phenyl (meth)acrylate; non-crosslinkable acrylamides such as acrylamide and methacrylamide; (meth)acrylic acid esters having non-crosslinkable tertiary amino groups such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; and styrene. These may be used alone or in combination of two or more.

[0033] Among the above, the (meth)acrylic acid ester copolymer in the present embodiment preferably contains acrylic acid, which corresponds to a monomer containing a carboxy group, as a monomer unit constituting the polymer. By containing acrylic acid in the (meth)acrylic acid ester copolymer, it becomes easy to adjust the average particle size of the obtained fine particles.

[0034] In the present embodiment, when the (meth)acrylic acid ester copolymer contains acrylic acid as a monomer unit constituting the polymer, the content is preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and more preferably 0.5% by mass or more. The content is preferably 30% by mass or less, particularly preferably 20% by mass or less, and more preferably 15% by mass or less. This makes it easy to adjust the average particle size of the resulting microparticles while ensuring a sufficient amount of the above-mentioned ethylene carbonate structure in the (meth)acrylic acid ester copolymer.

[0035] 2. Manufacturing method of fine particles The method for producing the microparticles according to the present embodiment is not particularly limited, but can be produced by a conventionally known polymerization method such as suspension polymerization, emulsion polymerization, seed polymerization, and dispersion polymerization. Among these, it is preferable to obtain the microparticles according to the present embodiment by emulsion-polymerizing a monomer unit containing the above-mentioned ethylene carbonate-containing acrylic monomer to produce an emulsion containing the above-mentioned (meth)acrylic acid ester polymer as a dispersoid, and then removing the dispersion medium constituting the emulsion and pulverizing the residue obtained. The microparticles according to the present embodiment may be aggregated. Even if aggregated, they can be pulverized while maintaining the appearance of the particle surface.

[0036] The emulsion polymerization may be carried out by a known method. For example, the emulsion polymerization may be carried out by stirring the ethylene carbonate-containing acrylic monomer, the other monomers as described above if desired, and an emulsifier in water as a dispersion medium, adding a polymerization initiator thereto, and stirring the mixture at a predetermined temperature.

[0037] The emulsifier is not particularly limited, but from the viewpoint of improving dispersion stability, anionic emulsifiers or nonionic emulsifiers are preferred, and anionic emulsifiers are more preferred.

[0038] Examples of anionic emulsifiers include sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, polyoxyethylene polycyclic phenyl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, and allyl alkyl sulfosuccinate. Examples of nonionic emulsifiers include polyoxyethylene alkyl ether and polyoxyethylene alkyl phenyl ether. Among these, polyoxyethylene polycyclic phenyl ether sulfate is particularly preferred. These emulsifiers may be used alone or in combination of two or more.

[0039] From the viewpoint of the stability of the emulsion polymerization reaction and the viewpoint of preventing the deterioration of physical properties due to the remaining unreacted emulsifier, the content of the emulsifier is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 mass of the total amount of all monomers. The content of the emulsifier is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 mass of the total amount of all monomers.

[0040] The polymerization initiator may be either water-soluble or oil-soluble, and examples thereof include azo compounds such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride and 2,2'-azobis(2-amidinopropane) dihydrochloride, persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate, and peroxides such as benzoyl peroxide, t-butyl hydroperoxide, and hydrogen peroxide. Redox initiators such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peracid and sodium ascorbate may also be used. The polymerization initiator may be used alone or in combination of two or more. Among these, ammonium persulfate is preferred from the viewpoint of excellent polymerization stability. These polymerization initiators may be used alone or in combination of two or more.

[0041] From the viewpoint of accelerating the polymerization rate, the content of the polymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the total amount of all monomers. The content of the polymerization initiator is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the total amount of all monomers.

[0042] The temperature and stirring conditions after the addition of the polymerization initiator may be any conditions that allow the dispersoid to be sufficiently dispersed, and for example, the temperature is preferably 60 to 90° C., particularly preferably 65 to 85° C., and more preferably 70 to 80° C. The stirring conditions are preferably 50 to 200 rpm, particularly preferably 70 to 180 rpm, and more preferably 100 to 150 rpm. The stirring time is preferably 10 to 60 minutes, particularly preferably 10 to 60 minutes, and more preferably 10 to 30 minutes.

[0043] Furthermore, it is preferable to further add an aqueous alkali solution such as aqueous ammonia, various water-soluble amines, an aqueous sodium hydroxide solution, or an aqueous potassium hydroxide solution to the emulsion obtained by emulsion polymerization to adjust the pH to 5 to 9, and particularly to 6 to 8.5. This makes it possible to improve the stability of the dispersion.

[0044] The solid content concentration of the obtained emulsion is preferably from 10 to 80% by mass, more preferably from 25 to 70% by mass, and further preferably from 45 to 65% by mass.

[0045] In the obtained emulsion, the particle size (D50) of the dispersoid composed of the (meth)acrylic acid ester copolymer is preferably 10 nm or more, more preferably 30 nm or more, particularly preferably 50 nm or more, and even more preferably 100 nm or more. The particle size (D50) is preferably 1 μm or less, particularly preferably 0.8 μm or less, and even more preferably 0.6 μm or less. When the particle size (D50) of the dispersoid is in the above range, it becomes easy to adjust the average particle size of the microparticles according to this embodiment to the range described later. Details of the method for measuring the particle size (D50) are as described in the examples described later.

[0046] The method for removing the dispersion medium from the emulsion obtained as described above is not particularly limited, and for example, the emulsion is left to stand under a predetermined temperature environment to dry the dispersion medium. In this case, the temperature is preferably 25°C or higher, particularly preferably 40°C or higher, and more preferably 45°C or higher. The temperature is preferably 100°C or lower, particularly preferably 90°C or lower, and more preferably 80°C or lower. Furthermore, the drying time is preferably 1 hour or more, particularly preferably 2 hours or more, and more preferably 3 hours or more. The time is preferably 72 hours or less, particularly preferably 48 hours or less, and more preferably 24 hours or less. As a method for removing the dispersion medium from the emulsion obtained as described above, filtration and centrifugation may be performed. In addition, the fine particles may be washed with water or various organic solvents for the purpose of removing the surfactant remaining on the surface of the fine particles.

[0047] As described above, by removing the dispersion medium from the emulsion, the dispersoid remains as a residue. The method for pulverizing this residue is not particularly limited and can be appropriately selected depending on the state of aggregation. For example, a dry pulverizing method such as mortar pulverization, hammer mill, jet mill, or bead mill can be used.

[0048] The average particle size of the microparticles obtained as described above is preferably 10 nm or more, particularly preferably 20 nm or more, and more preferably 30 nm or more. The average particle size is preferably 1 μm or less, particularly preferably 0.9 μm or more, and more preferably 0.8 μm or less. When the average particle size is within the above range, the microparticles according to this embodiment have better versatility. For example, when the microparticles according to this embodiment are added to a composition, the microparticles are easily mixed and dispersed well. The average particle size of the microparticles is measured by observation using a scanning electron microscope, and the details are as described in the examples below.

[0049] In addition, when the content of the ethylene carbonate-containing acrylic monomer in the (meth)acrylic acid ester copolymer is 90% by mass or more and the average particle diameter of the particles is 100 nm or more, the particles according to this embodiment can exhibit any structural color due to Bragg reflection corresponding to the particle diameter, and various colors can be produced by controlling the particle diameter. Therefore, the resin film formed from the resin composition containing the particles according to this embodiment also has structural coloring properties and is suitable as a material for an article exhibiting a structural color, and is suitable for improving the design of the article.

[0050] 3. How to use the microparticles The fine particles according to the present embodiment can be used, for example, as a foaming agent, an antiblocking agent, a slipping agent, a light diffusing agent, etc. for a resin film (coat layer, adhesive layer, resin film, etc.), although the applications are not particularly limited. The resin film will be described in detail later.

[0051] [Resin composition and article] Another embodiment of the present invention relates to a resin composition containing the above-mentioned fine particles, and an article including a resin film formed from the resin composition.

[0052] In the resin composition, the components other than the fine particles according to the present embodiment can be appropriately selected according to the type of resin film to be formed. For example, when forming a pressure-sensitive adhesive layer as the resin film, the resin composition preferably contains a pressure-sensitive adhesive component as the main material, and examples thereof include acrylic pressure-sensitive adhesives (acrylic polymers) and the like. In addition, when forming a coating layer (such as a surface coating layer or an anchor coating layer) as the resin film, the resin composition preferably contains a curable component or the like as the main material. In addition, when forming a resin film as the resin film, the resin composition contains a thermoplastic resin or the like as the main material, and the fine particles according to the present embodiment can be dispersed in advance in the thermoplastic resin and used as a master batch.

[0053] In addition, when the fine particles according to the present embodiment are used as a foaming agent, the resin composition preferably contains a catalyst that promotes the decomposition of the ethylene carbonate structure described above, from the viewpoint of enabling efficient release of carbon dioxide. As an example of the catalyst, the nucleophilic anion generator described above is particularly preferable.

[0054] The nucleophilic anion generator is not particularly limited as long as it generates a nucleophilic anion by heating and can sufficiently release carbon dioxide gas from the ethylene carbonate structure contained in the pressure-sensitive adhesive composition according to the present embodiment by the nucleophilic anion. Examples of the nucleophilic anion include fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ), hydroxide ion (OH - ) and the like, and among these, fluoride ions (F - ) and bromide ion (Br - ) is preferred, and fluoride ion (F - Examples of the cation constituting the nucleophilic anion generator include a quaternary ammonium cation, an imidazolium cation, a pyrrolidinium cation, a pyridinium cation, a piperidinium cation, a phosphonium cation, an alkali metal ion, an alkaline earth metal ion, and the like, and among these, a quaternary ammonium cation is preferred.

[0055] Specific preferred examples of the nucleophilic anion generator include tetrabutylammonium fluoride (TBAF), tetrabutylammonium bromide (TBAB), 1-ethyl-3-methylimidazolium bromide, tetrabutylphosphonium bromide, sodium hydroxide, etc., and among these, tetrabutylammonium fluoride (TBAF) and tetrabutylammonium bromide (TBAB) are preferred. These nucleophilic anion generators may be used alone or in combination of two or more.

[0056] The resin film is not particularly limited as long as it is formed from a resin composition containing the fine particles according to the present embodiment. More specific examples of the resin film include a pressure-sensitive adhesive layer, a resin film, and a surface coat layer or an anchor coat layer formed on the surface of a specific substrate.

[0057] The above-mentioned article depends on the type of resin film, for example, when the resin film is a pressure-sensitive adhesive layer, it is a pressure-sensitive adhesive sheet. When the resin film is a surface coating layer, the article can be a hard coat film having a substrate film and a surface coating layer provided on the substrate. When the resin film is a resin film, the article can be a pressure-sensitive adhesive sheet or hard coat film having the resin film, or a substrate film consisting of only the resin film.

[0058] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0060] Example 1 A solution containing 20 parts by mass of an ethylene carbonate-containing acrylic monomer (monomer produced using carbon dioxide as a raw material; 2-oxo-1,3-dioxolan-4-yl)methyl methacrylate) in which n is 2 in the above-mentioned formula (3), 0.2 parts by mass of acrylic acid, 1 part by mass of polyoxyethylene polycyclic phenyl ether sulfate salt (manufactured by Nippon Nyukazai Co., Ltd., product name "Newcol 707SF") as an emulsifier, and 65 parts by mass of purified water was stirred at 70°C and 170 rpm.

[0061] Next, 0.3 parts by mass of ammonium persulfate (APS) was added to the above solution as a polymerization initiator, and the mixture was polymerized for 10 minutes by emulsion polymerization while stirring at 70° C. and 160 rpm to prepare a (meth)acrylic acid ester polymer. This resulted in an emulsion in which the (meth)acrylic acid ester polymer was dispersed as a dispersoid in water as a dispersion medium.

[0062] In the obtained emulsion, the mass ratio of the ethylene carbonate-containing acrylic monomer constituting the (meth)acrylic acid ester polymer (A) to acrylic acid was about 99:1, and the molar ratio was about 37:1. The solid content concentration of the above emulsion was calculated to be 14.4% by mass. Furthermore, the particle size distribution of the dispersoid ((meth)acrylic acid ester polymer) in the emulsion was measured by DLS method, and the particle size (D50) was 260 nm.

[0063] The emulsion obtained as described above was left to stand overnight in an environment of 50°C to dry the dispersion medium. The residue remaining after drying was pulverized in a mortar to obtain fine particles. The fine particles were vapor-deposited with osmium and then observed with a scanning electron microscope (SEM). The observation results are shown in Figure 1. The obtained image was subjected to circle detection and binarization processing using image analysis software, the circle equivalent diameter of each particle was measured, and a histogram of the particle size distribution of the fine particles was created. The average particle size was calculated from the histogram and was found to be 236 nm.

[0064] [Examples 2 to 5] Emulsions were prepared in the same manner as in Example 1, except that the composition of the (meth)acrylic acid ester polymer, the content of the ethylene carbonate-containing acrylic monomer in the (meth)acrylic acid ester polymer, the content of the emulsifier, and the content of purified water were changed as shown in Table 1. The solid concentration and particle size (D50) of each of the obtained emulsions were calculated, and were as shown in Table 1. The average particle size of the obtained fine particles was measured in the same manner as in Example 1, and the average particle size of each was as shown in Table 1.

[0065] Example 6 A solution containing 5 parts by mass of 4-(oxiran-2-ylmethoxy)butyl acrylate, 0.32 parts by mass of lithium bromide, and 24 parts by mass of N-N'-dimethylformamide was replaced with carbon dioxide gas in the system and then stirred at 60°C for 17 hours. After distilling off the N-N'-dimethylformamide under reduced pressure, ethyl acetate and purified water were added, followed by extraction and washing, and magnesium sulfate was added to the resulting organic layer for drying. After filtration, the ethyl acetate was distilled off under reduced pressure to obtain a pale yellow liquid (yield 96%).

[0066] The components in the resulting pale yellow liquid were subjected to 1H NMR and 13C NMR measurements, and were confirmed to be the ethylene carbonate-containing acrylic monomer (4-((2-oxo-1,3-dioxolan-4-yl)methoxy)butyl acrylate) in which n is 1 and m is 4 in the above-mentioned formula (4).

[0067] A solution containing 15 parts by mass of ethylene carbonate-containing methacrylic monomer (monomer produced using carbon dioxide as a raw material) in which n is 1 in the above-mentioned formula (3), 5 parts by mass of ethylene carbonate-containing acrylic monomer (monomer produced using carbon dioxide as a raw material) in which n is 1 and m is 4 in the above-mentioned formula (4) prepared as described above, 0.8 parts by mass of acrylic acid, 1 part by mass of polyoxyethylene polycyclic phenyl ether sulfate salt (manufactured by Nippon Nyukazai Co., Ltd., product name "Newcol 707SF") as an emulsifier, and 130 parts by mass of purified water was stirred under conditions of 70°C and 170 rpm.

[0068] Next, 0.3 parts by mass of ammonium persulfate (APS) was added to the above solution as a polymerization initiator, and the mixture was polymerized for 10 minutes by emulsion polymerization while stirring at 70° C. and 160 rpm to prepare a (meth)acrylic acid ester polymer. This resulted in an emulsion in which the (meth)acrylic acid ester polymer was dispersed as a dispersoid in water as a dispersion medium.

[0069] In the obtained emulsion, the mass ratio of the ethylene carbonate-containing acrylic monomer constituting the (meth)acrylic acid ester polymer (A) to acrylic acid was about 96: 4, and the molar ratio was about 8.7: 1. The solid content concentration of the above emulsion was calculated to be 15.8 mass%.

[0070] Details of the abbreviations and other information in Table 1 are as follows: ECMA: (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate ECMBA: 4-((2-oxo-1,3-dioxolan-4-yl)methoxy)butyl acrylate AAc: acrylic acid MMA: Methyl methacrylate

[0071] Comparative Example 1 An emulsion was prepared in the same manner as in Example 1, except that only methyl methacrylate monomer was used and the content of the emulsifier and the content of the purified water were changed as shown in Table 1. The solid content of the obtained emulsion was calculated and found to be as shown in Table 1. The particle size distribution of the dispersoid in the obtained emulsion was measured in the same manner as in Example 1, and the particle size (D50) was found to be as shown in Table 1.

[0072] Furthermore, from the emulsion obtained as described above, fine particles were obtained in the same manner as in Example 1. When the fine particles were observed with a scanning electron microscope in the same manner as in Example 1, the average particle size was as shown in Table 1.

[0073] [Test Example 1] (Calculation of CO2 fixation amount) The amount (mass ratio) of carbon dioxide used (fixed) in the emulsion was calculated as the amount of CO2 fixed from the blending amount of ethylene carbonate-containing acrylic monomer in the microparticles obtained in the Examples and Comparative Examples. Specifically, the molecular weight of CO2 (=44) was divided by the molecular weight of ethylene carbonate-containing acrylic monomer (A) (=158) and expressed as a percentage. The results are shown in Table 1.

[0074] [Test Example 2] (Observation of structural color) The fine particles obtained in the examples and comparative examples were visually observed by a number of evaluators and evaluated for the color tone of the structural color. The evaluation results are shown in Table 1.

[0075] [Table 1]

[0076] As shown in Table 1, it was confirmed that in the examples, fine particles with a particle size of 66 nm to 361 nm were obtained. It was also confirmed that the fine particles of Examples 1 to 2 and 4 to 5 have structural coloring, and it was understood that the color of the observed structural color changes when the particle size changes. In addition, the ethylene carbonate-containing acrylic monomer is a monomer produced using carbon dioxide as a production raw material, and therefore has a small environmental impact. [Industrial Applicability]

[0077] The microparticles of the present invention can fix carbon dioxide and are useful for environmental protection. The microparticles of the present invention are useful for a wide range of applications, such as additives for antiblocking agents, toner additives, powder paints, water-dispersed paints, decorative plate additives, artificial marble additives, cosmetic fillers, chromatography column fillers, and matting agents, for resin films, paints, adhesives, and pressure sensitive adhesives. The microparticles of the present invention have structural coloring properties, and are therefore suitable as materials for structural color-exhibiting objects. The microparticles of the present invention are decomposed by heat treatment with a catalyst to release carbon dioxide, and are therefore suitable for use in the manufacture of products that require easy dismantling.

Claims

1. As a monomer unit constituting the polymer, 【Chemistry 1】 The fine particles contain a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the formula:

2. 2. The fine particles according to claim 1, wherein the (meth)acrylic acid ester polymer contains, as a monomer unit constituting the polymer, the ethylene carbonate-containing monomer in an amount of 50% by mass or more and 99.9% by mass or less.

3. 2. The fine particles according to claim 1, wherein the ethylene carbonate-containing acrylic monomer is a compound represented by the following formula (2) or (3): 【Chemistry 2】 (In the formula, n represents an integer of 0 or more.) 【Chemistry 3】 (In the formula, n represents an integer of 0 or more.)

4. 2. The fine particles according to claim 1, wherein the (meth)acrylic acid ester polymer contains acrylic acid as a monomer unit constituting the polymer.

5. 2. The fine particles according to claim 1, having an average particle size of 10 nm or more and 1 μm or less.

6. The microparticle according to claim 1, characterized in that it is obtained by emulsion-polymerizing a monomer unit containing the ethylene carbonate-containing acrylic monomer to produce an emulsion containing the (meth)acrylic acid ester polymer as a dispersoid, and then removing a dispersion medium constituting the emulsion to obtain a residue, and pulverizing the residue.

7. A resin composition comprising the fine particles according to any one of claims 1 to 6.

8. An article comprising a resin film formed from the resin composition according to claim 7.

9. The resin film is a pressure-sensitive adhesive layer, The article is a pressure-sensitive adhesive sheet.

9. The article of claim 8.

Citation Information

Patent Citations

  • JP214208A